THE VIRTUAL WORLD AND ITS OBJECTS FROM THE PERSPECTIVE OF PRIVATE LAW REGULATION IN THE REPUBLIC OF UZBEKISTAN - Эгамбердиев Эдуард Хажибаевич (American Journals, 2023)
The article analyzes the problems of determining the legal status of the virtual world and objects in it, examines the theories of virtual property and gives the relationship between property rights and intellectual property to regulate relations arising in the virtual world.
Keywords: virtual property , real world, virtual world, property law, private law, computer code.